Effect of Quorum Quenching Lactonase in Clinical Isolates of Pseudomonas aeruginosa and Comparison with Quorum Sensing Inhibitors - Guendouze, Assia; Plener, Laure; Bzdrenga, Janek; Jacquet, Pauline; Rémy, Benjamin; Elias, Mikael; Lavigne, Jean-Philippe; Daudé, David; Chabrière, Eric (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is a Gram negative pathogenic bacteria involved in many human infections including otitis, keratitis, pneumonia and diabetic foot ulcers. P. aeruginosa uses a communication system, referred to as quorum sensing (QS), to adopt a group behaviour by synchronizing the expression of certain genes. Among the regulated traits, secretion of proteases or siderophores, motility and biofilm formation are mainly involved in the pathogenicity. Many efforts have been dedicated to the development of quorum sensing inhibitors (QSI) and quorum quenching (QQ) agents to disrupt QS. QQ enzymes have been particularly considered as they may act in a catalytic way without entering the cell. Here we focus on the lactonase SsoPox which was previously investigated for its ability to degrade the signalling molecules, acyl-homoserine lactones, in particular on the engineered variant SsoPox-W263I. We highlight the potential of SsoPox-W263I to inhibit the virulence of 51 clinical P. aeruginosa isolates from diabetic foot ulcers by decreasing the secretion of two virulence factors, proteases and pyocyanin, as well as biofilm formation. We further compared the effect of SsoPox-W263I to the comprehensively described QSI, 5-fluorouracil and C-30. We found the lactonase SsoPox-W263I to be significantly more effective than the tested QSI at their respective concentration optimum and to retain its activity after immobilisation steps, paving the way for future therapeutic applications.